Analisis Risiko dan Kepatuhan dalam Keputusan Kantor Akuntan Publik untuk Menerima Klien Berisiko Tinggi - Ratnadewati, Nabilla Carissa; Izzalqurny, Tomy Rizky (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
The decision of the Public Accounting Firm (KAP) to accept high-risk clients presents strategic challenges that have the potential to affect audit quality and professional reputation. This study aims to analyze the risk and compliance factors that influence KAP's decision to accept high-risk clients. The method used is a qualitative study with an in-depth interview approach to auditors at one of the leading KAPs in Jakarta. The results showed that the main risks include potential violations of auditor independence, non-compliance with legal standards, and challenges in implementing a risk-based audit approach. To mitigate these risks, intensive procedures such as the use of analytic technology and consultation with external experts are implemented. The findings emphasize the need for integrated risk management and tiered internal controls to ensure audit quality and safeguard KAP's reputation.